Thrombolyic and Vasodilator Treatment in a Patient With Prolonged Retinal Ischemia. Issue 3 (May 2017) - Sista, Sri Raghav; Pula, John H.; Reddy, Deepak; Abdo, Chris; Parker, Sarah; Getz, Mark A.; Kattah, Jorge C.
Abstract : Vasospastic transient monocular vision loss associated with systemic lupus erythematosus and antiphospholipid syndrome is typically short lasting and responsive to vasodilators. Virchow's triad of endothelial dysfunction, arterial stasis, and a hypercoagulable state are factors in systemic lupus erythematosus/antiphospholipid syndrome that may potentially contribute to prolonged retinal hypoperfusion and central retinal artery occlusion. Consequently, rapid intervention to address all components of Virchow's triad may increase the probability of a good outcome. Time of retinal viability should guide the management strategy. We report a systemic lupus erythematosus/antiphospholipid syndrome patient with prolonged monocular blindness coinciding with retinal arterial narrowing and rouleaux formation who responded favorably to sequential use of vasodilators and intravenous thrombolysis, addressing each component of Virchow's triad.